Thermal Activated of Indonesian Bentonite as A Low-Cost Adsorbent for Procion Red Removal from Aqueous Solution - Tarmizi Taher; Dedi Rohendi; Risfidian Mohadi; Aldes Lesbani (Chemistry Department, The University of Brawijaya, 2018)
Abundant and inexpensive Indonesian natural bentonite was activated by thermal activation at 500 oC for removal of procion red dye as one of the most used synthetic dye in the traditional songket fabric production around Palembang city. Activated bentonite product was characterized by FT-IR, XRD, and thermal analysis. The adsorption process was conducted in batch adsorption system by applying various adsorption parameter condition including, initial pH condition, contact time, and initial dye concentration. The activated bentonite characterization indicates that during the activation process, the structure of the original bentonite was not changed significantly and the result of the thermal analysis revealed that thermal activation at 500 oC was draining the water content without destructing the silica-alumina framework of bentonite. The adsorption kinetics study shows that the procion red adsorption into the activated bentonite follows the pseudo-second order kinetic model. The isotherm adsorption study revealed that procion red adsorption into activated bentonite adapted the Langmuir adsorption isotherm.